Coverage of citizen health screening program and prevalence of selected non-communicable diseases in Rukum West District of Nepal - Poudel, Om Prakash; Khadka, Rabin; KC, Prakash; Sharma, Kiran; Bashyal, Bhanu Bhakta (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Non-communicable diseases (NCDs) are the leading cause of the global burden of disease. With the increasing burden of NCDs, gaps persist in the care continuum for NCD services. The Citizen Health Screening Program (CHSP) was implemented by the Health Service Directorate in accordance with guidelines approved by the Ministry of Social Development, Karnali Province. The aim of the program was to screen for Non-Communicable Diseases among the elderly population and to ensure access to health services for management.Methods: This retrospective cross-sectional study analyzed secondary data from the Citizen Health Screening Program in Rukum West, Nepal. Conducted over seven months, it screened individuals aged 55 and above for hypertension, raised blood sugar, and possible kidney disorders. Data collection followed standardized protocols to measure hypertension, raised blood sugar, and possible kidney disorders, with trained government health workers. Descriptive analysis was performed using Excel and STATA.Results: The screening covered 78% of the target population, identifying hypertension (15.2%), raised blood sugar (12.2%), and possible kidney disorders (12.5%). Hypertension, raised blood sugar, and possible kidney disorders were higher among females and increased with age. The hypertension, diabetes, and possible kidney disorders varied across local levels, with Musikot urban municipality, Tribeni rural municipality, and Sanibheri rural municipality showing the highest rates, respectively.Conclusion: The study highlights a significant NCD burden, with higher prevalence in women and older adults. Expanding screening to younger populations and implementing targeted interventions are essential to enhance prevention and management efforts in Rukum West, Nepal.